Numerical investigation of electronic component cooling with natural convection in a vented cavity - Koca, Ahmet (My University, 2008)
In this study, natural convection problem in a rectangular cavity with a heat source on lower wall and ventilation on a side wall was investigated numerically. Two-dimensional continuity, momentum and energy equations were solved by the method of finite difference. Heat transfer and fluid flow in steady-state condition were studied by assuming insulated of upper and horizontal walls of cavity. The numerical results were discussed with plots of streamlines, isotherms, velocity profiles and variation of Nusselt number. Length of heat source, length and position of ventilation and Rayleigh number effects were investigated. It was found that length of heat source and length and position of ventilation have significant effect on heat transfer and fluid flow. Heat transfer increased with the increasing of ventilation length, heat source length and Rayleigh number.
Havalandirmali bi?r kanaldakí elektroni?k elemanin do?al konveksi?yonla so?utulmasinin sayisal olarak i?ncelenmesi?
Keywords: Electronic cooling; Natural convection; Numerical solution; Vented cavity